1996
DOI: 10.3109/08990229609051397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hindpaw Position in Rats during Chronic Constriction Injury (CCI) Produced with Different Suture Materials

Abstract: Bennett and Xie (1988) described an experimental peripheral neuropathy that is produced by loosely ligating a rat's left sciatic nerve with chromic gut suture. Four ligations, which are tied tightly enough to constrict the nerve and retard epineurial blood flow, produce a chronic constriction injury (CCI). Maves et al. (1993) reported that if the ligations are tied more loosely (i.e., no retardation of blood flow) than those that produce the CCI, rats exhibit postural changes only when the ligations are of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Many studies have demonstrated a dependence of radicular pain on mechanical and chemical inputs (Kawakami et al, 1994a,b;Kajander et al, 1996;Olmarker et al, 1997;Hashizume et al, 2000;Olmarker et al, 2002;Hou et al, 2003;Winkelstein and DeLeo, 2004;Cornefjord et al, 2004;Hubbard and Winkelstein, 2005). This study is the first to our knowledge to examine such factors of chemical irritation and nerve root compression for transient loading to the cervical nerve roots.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies have demonstrated a dependence of radicular pain on mechanical and chemical inputs (Kawakami et al, 1994a,b;Kajander et al, 1996;Olmarker et al, 1997;Hashizume et al, 2000;Olmarker et al, 2002;Hou et al, 2003;Winkelstein and DeLeo, 2004;Cornefjord et al, 2004;Hubbard and Winkelstein, 2005). This study is the first to our knowledge to examine such factors of chemical irritation and nerve root compression for transient loading to the cervical nerve roots.…”
Section: Discussionmentioning
confidence: 94%
“…While autologous disc material may be a clinically relevant model of the local injury scenario, such approaches present logistical challenges and do not enable separation of the specific and relative effects of either the mechanical and/or chemical contributions of the insult. As such, lumbar radiculopathy models have also separated these injury components to investigate their effects on behavioral hypersensitivity (Olmarker et al, 1993;Maves et al, 1993;Kawakami et al, 1994a,b;Kajander et al, 1996;Colburn et al, 1999;Hashizume et al, 2000;Hou et al, 2003;Murata et al, 2004;Winkelstein and DeLeo, 2004;Hubbard and Winkelstein, 2005). Though radicular pain models implement ligation with chromic gut to simultaneously apply compression and chemical irritation in low back pain (Maves et al, 1993;Kawakami et al, 1994a,b;Kajander et al, 1996;Xu et al, 1996;Colburn et al, 1999;Hashizume et al, 2000;Winkelstein and DeLeo, 2004;Robinson and Meert, 2005), mechanistic information for cervical disc herniation is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Methodological variables could account for this discrepancy. For example, we used a different suture material than that used in any previous reports and the use of different types of suture materials has been shown to produce different outcomes (Kajander et al, 1996). Secondly, several laboratories report thermal and mechanical stimulus-evoked responses as a difference score, subtracting the number of responses made by the ligated hindpaw from that of the un-operated hind paw.…”
Section: Behavioral Effects Of Chronic Constriction Injurymentioning
confidence: 99%
“…Some investigators may find it easier to perform surgery on a specific side due to handedness, whilst others have switched sides within experiments to rule out any bias. It is noteworthy that several variations to the original procedure have been reported including using only 2 ligatures around the nerve 16,17 and using suture material other than chromic gut such as plain gut and polyglactin (vicryl) 18,19 in rats. In addition, the CCI model has also been modified for use in mice, where the procedure is identical, except for the use of 2-3 ligatures with various suture materials including chromic gut, nylon, and prolene 15,20,21 .…”
mentioning
confidence: 99%